Development of Local Wisdom-Based Instructional Materials to Enhance Reading Skills of Fifth-Grade Elementary School Students - Paulina Reta Paulina; Unik Ambar Wati; Marwan Marwan; Devi Anggi Friani; Agus Herwanto; Wayan Pudma Febby Mandalika (STAI Hubbulwathan Duri, 2025)
Indonesia is currently experiencing a critical literacy crisis, particularly in frontier, outermost, and disadvantaged regions. Contributing factors include limited access to reading materials, ineffective library management, and declining student engagement in literacy activities. This study aimed to develop Indonesian language teaching materials incorporating local wisdom stories to enhance the reading skills of fifth-grade elementary students. A Research and Development (RD) approach was adopted, utilizing the ADDIE model encompassing five phases: analysis, design, development, implementation, and evaluation. The study was conducted at SD Negeri 15 Melayang, involving 21 students and 3 teachers. Data were collected using observations, interviews, questionnaires, and standardized reading tests. Analytical techniques included descriptive statistics, normality and homogeneity tests, paired sample t-tests, and independent sample t-tests. The developed teaching materials received favorable evaluations, with content experts rating them at 83.32% and media experts at 80.31%. Practical implementation scores were also high, with students giving 83.55% and teachers 90.97%. Statistical analysis revealed a significant improvement in students’ reading skills following the intervention, with a p-value of 0.001. These results demonstrate that Indonesian language teaching materials infused with local wisdom effectively enhance reading proficiency among fifth-grade students. The integration of culturally relevant narratives supports improved engagement and learning outcomes, offering a promising solution to Indonesia’s literacy challenges.